2017
DOI: 10.1371/journal.pone.0179915
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of pig movements: Loyalty patterns and contact chains of different holding types in Denmark

Abstract: Understanding animal movements is an important factor for the development of meaningful surveillance and control programs, but also for the development of disease spread models. We analysed the Danish pig movement network using static and temporal network analysis tools to provide deeper insight in the connection between holdings dealing with pigs, such as breeding and multiplier herds, production herds, slaughterhouses or traders. Pig movements, which occurred between 1st January 2006 and 31st December 2015 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Based on simulation models and network analyses, previous work has shown that pig movements and herd types are likely to play important roles in the spread of swine diseases in Denmark ( 4 , 8 ). In addition, several small-scale studies from Denmark and the Netherlands have found that the LA-MRSA CC398 status of a given pig farm depends largely on the LA-MRSA CC398 status of its suppliers ( 10 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on simulation models and network analyses, previous work has shown that pig movements and herd types are likely to play important roles in the spread of swine diseases in Denmark ( 4 , 8 ). In addition, several small-scale studies from Denmark and the Netherlands have found that the LA-MRSA CC398 status of a given pig farm depends largely on the LA-MRSA CC398 status of its suppliers ( 10 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the rapid spread of LA-MRSA CC398 within the Danish pig production system was caused by clonal expansion of the three lineages. Breeding herds are considered a critical factor in the spread of swine diseases because they produce and supply hybrid breeding pigs to a large number of production holdings ( 4 ). Thus, it is possible that the emergence of the same lineages in breeding farms somewhere between 2008 and 2014 has accelerated the spread of LA-MRSA CC398 within the Danish pig production system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Network analysis has been described as a useful methodology to characterize pigs movements, and the impact that the contact structure has on the spread of diseases (Lentz et al, ; Schulz, Boklund, Halasa, Toft, & Lentz, ; Sterchi et al, ) in countries such as Canada (Dorjee et al, ; Thakur et al, ), the USA (Lee et al, ), Germany (Büttner, Krieter, & Traulsen, ), France (Salines et al, ) and Kenya and Uganda (Lichoti et al, ). When comparing these studies to our results, we realize that Argentinean networks have a smaller diameter (2–6) than networks in the USA, Canada, France, Germany, Kenya and Uganda: 9, 3.25, 6 to 20 and 7, respectively.…”
Section: Discussionmentioning
confidence: 99%